1992
DOI: 10.1177/019459989210700307
|View full text |Cite
|
Sign up to set email alerts
|

Partial Endoscopic Middle Turbinectomy Augmenting Functional Endoscopic Sinus Surgery

Abstract: Endoscopic sinus surgery has gained acceptance in the otolaryngologic community as an effective and safe method of treating inflammatory disease of the paranasal sinuses. At our institution, partial endoscopic middle turbinectomy has become a standard component of the procedure and our experience is reported. Middle turbinectomy enhances surgical exposure, specific anatomic anomalies are more completely corrected, and subpopulations of patients at risk for failure because of their underlying disease enjoy decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
51
0
1

Year Published

1996
1996
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(57 citation statements)
references
References 16 publications
5
51
0
1
Order By: Relevance
“…1188,1196,1197 One retrospective study in 1992 initially found no effect, but when synechiae that might lead to maxillary stenosis were included, there was a positive effect for MT resection. 1198 It appears from these data that MT resection has no significant effect on middle meatal antrostomy patency following ESS.…”
Section: Xd3 Surgical Principles/techniques-mt Preservation or Resmentioning
confidence: 79%
“…1188,1196,1197 One retrospective study in 1992 initially found no effect, but when synechiae that might lead to maxillary stenosis were included, there was a positive effect for MT resection. 1198 It appears from these data that MT resection has no significant effect on middle meatal antrostomy patency following ESS.…”
Section: Xd3 Surgical Principles/techniques-mt Preservation or Resmentioning
confidence: 79%
“…12 Many surgical techniques of safe partial MT resection are described to avoid lateralization of MT remnant. [12][13][14] According to the study by Giacchi et al, 12 anterior/inferior one-third to one-half of the turbinate should be removed while preserving superior and lateral attachments. Other authors 13,14 prefer to preserve superior half of the MT.…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14] According to the study by Giacchi et al, 12 anterior/inferior one-third to one-half of the turbinate should be removed while preserving superior and lateral attachments. Other authors 13,14 prefer to preserve superior half of the MT. In our study the mean length of the MT was measured between the anterior attachments of the middle and superior turbinate, this length attaches the MT to the lateral nasal wall.…”
Section: Discussionmentioning
confidence: 99%
“…LaMear et al 4 reported a retrospective series of 298 patients studied during 4 years to assess the safety and efficacy of partial MT resection during FESS. In the initial analysis, the outcomevariablesofinterestweresynechia formation and antrostomy patency.…”
Section: Promentioning
confidence: 99%
“…No major complications attributable to MT resection, including atrophic rhinitis, were encountered in this series. 4 Vleming et al 5 were operated on after FESS to assess the major and minor complication rates. The authors noted 15 patients (1.2% of operated sides) with significant postoperative synechia formation in the overall series, and all of the sides with synechia that had been operated on had an intact MT (eg, had not undergone MT resection).…”
Section: Promentioning
confidence: 99%